Effects of commercially formulated water on the hydration status of dehydrated collegiate wrestlers - Valiente, J. S.; Utter, A. C.; Quindry, J. C.; Nieman, D. C. (The Journal of Strength and Conditioning Research, 2009)
The objective of this study was to evaluate the effects of three different drinks (commercially formulated water, bottled water, and a carbohydrate-electrolyte beverage) on blood and urinary markers of hydration after acute dehydration in collegiate wrestlers. Twenty-one athletes were recruited to perform a randomized, crossover study comparing the effectiveness of commercially formulated water, carbohydrate-electrolyte (6% or 60 g·L-1), or regular bottled water (placebo) in promoting rehydration after a 3% reduction in body mass. Urine specific gravity (Usg), urine osmolarity (Uosm), plasma osmolarity (Posm), and plasma volume were measured pre- and post-dehydration and at 1 hour after rehydration. Statistical analyses used a 3 (conditions) × 3 (times) repeated measures analysis of variance. Significant (p < 0.01) interactions were found for Posm, Uosm, and Usg. Posm returned to baseline levels and Uosm remained in a lower balance after 1 hour of rehydration in the trials of the commercially formulated water and regular bottled water. No significant interactions were found for plasma volume shift. The findings of this study demonstrate that the commercially formulated water was no more effective in promoting rehydration than either a carbohydrate-electrolyte solution or plain water in collegiate wrestlers after a 3% reduction in body mass and a rehydration period of 1 hour when consuming 100% of their body weight loss.